2001
DOI: 10.1002/cne.1404
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the AMPA subunit GluR2 in the outer plexiform layer of goldfish retina

Abstract: L-glutamate, the photoreceptor neurotransmitter, depolarizes horizontal cells and OFF bipolar cells by ionotropic AMPA-glutamate receptors. The AMPA-receptor subunit (GluR4) is localized to dendrites of OFF bipolar cells in goldfish retina. Here, we used immunohistochemical techniques to identify AMPA-receptor subunits on horizontal cell dendrites. A monoclonal antibody against rat GluR2, with high sequence homology to the recently cloned goldfish GluR2a receptor, was used for light- and electron-microscopical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 64 publications
6
34
0
2
Order By: Relevance
“…Note the punctate appearance of GAD67-IR in the horizontal cell dendrites, indicating a concentration of reaction product in parts of the dendrite rather than a uniform distribution. This finding is consistent with our EM studies in goldfish showing that GluR2-IR is found in horizontal cell dendrites (Klooster et al, 2001). Thus, we are able to use GluR2-IR as a marker to identify structures as HI dendrites and by exclusion, those that were not.…”
Section: Gad67/giur2supporting
confidence: 92%
See 3 more Smart Citations
“…Note the punctate appearance of GAD67-IR in the horizontal cell dendrites, indicating a concentration of reaction product in parts of the dendrite rather than a uniform distribution. This finding is consistent with our EM studies in goldfish showing that GluR2-IR is found in horizontal cell dendrites (Klooster et al, 2001). Thus, we are able to use GluR2-IR as a marker to identify structures as HI dendrites and by exclusion, those that were not.…”
Section: Gad67/giur2supporting
confidence: 92%
“…The GluR2-IR structures in goldfish were identified, by pre-embedding electron microscopic immunocytochemistry (EM-ICC), as belonging to the distal tips of rod and cone horizontal cells. All cones were innervated by GluR2-IR dendrites (Klooster et al, 2001). Preliminary EM-ICC in this laboratory (Klooster & Yazulla, unpublished) confirms that GluR2-IR is localized to cone horizontal cell dendrites in the zebrafish as well.…”
Section: Glycinergic Systemsupporting
confidence: 50%
See 2 more Smart Citations
“…Expression of AMPA receptor subunits 3 and 4 in the horizontal cells was observed in rat and cat (Hamassaki-Britto et al, 1993). In contrast to these results, immunohistochemical analysis in adult zebrafish also revealed expression of gria2 genes in horizontal cells , as also observed in goldfish (Vandenbranden et al, 2000;Klooster et al, 2001) and expression of gria4 in Mueller and bipolar cells but not in horizontal cells ). Those differences can be explained with a change in the expression pattern later during development.…”
Section: Discussionmentioning
confidence: 57%